DORIVOR O‘SIMLIKLARDAN FOYDALANISH TARIXI - Po‘latov , Sarvar Mustafoevich; Najimova , Dilafruz Nabijon qizi (Educational Research in Universal Sciences, 2023)
The rapid development of the pharmaceutical industry in the Republic of Uzbekistan causes a sharp increase in the demand for raw materials of medicinal plants. Due to the limited resources of naturally growing medicinal plants, the pharmaceutical industry’s demand for medicinal plant raw materials can be met mainly by growing medicinal plants. Until now, medicinal plants and their growing technologies have not been fully developed in the specialized farms of our country, farmers, foresters, peasants and other types of ownership, and are being cared for without scientific basis. For this reason, providing the pharmaceutical industry with high-quality, abundant, low-cost and environmentally friendly raw materials remains a big problem. This situation, of course, requires the provision of farms engaged in the cultivation of raw materials of medicinal plants with experts who have mastered the technologies of growing medicinal plants.